Developing the Pediatric Gastrointestinal Endoscopy Unit: A Clinical Report by the Endoscopy and Procedures Committee. Issue 2 (August 2016) - Pall, Harpreet; Lerner, Diana; Khlevner, Julie; Reynolds, Carrie; Kurowski, Jacob; Troendle, David; Utterson, Elizabeth; Evans, Pamela M.; Brill, Herbert; Wilsey, Michael; Fishman, Douglas S.
Abstract : Supplemental Digital Content is available in the text Abstract : ABSTRACT: There is significant variability in the design and management of pediatric endoscopy units. Although there is information on adult endoscopy units, little guidance is available to the pediatric endoscopy practitioner. The purpose of this clinical report, prepared by the NASPGHAN Endoscopy and Procedures Committee, is to review the important considerations for setting up an endoscopy unit for children. A systematic review of the literature was undertaken in the preparation of this report regarding the design, management, needed equipment, motility setup, billing and coding, and pediatric specific topics.